Construction analysis of predictor variables that explain labor turnover problems among millennials employees - Budhi Santosa, Agus (International Journal of Applied Finance and Business Studies, 2024)
Turnover is a problem for which no solution or prevention has yet been found, because there is no measuring tool that can be used to predict turnover. So this research aims to construct variables as predictors for analyzing the potential turnover of millennial employees, as well as testing external factors such as management systems and work environments as well as individual factors as variables that influence turnover in millennial employees. The research, which took 86 millennial employee respondents from five manufacturing companies in East Java, was measured using the General Aptitude Test Battery (GATB) and Minnesota Importance Questionnaire (MIQ) as predictors. Data analysis used descriptive statistics and testing used analysis of variance (Anava) which proves that external factors, namely job expansion and work environment, have probability values that construct external factors and influence the emergence of turnover in millennial employees, as well as probability values for individual factors that are constructed The variables of workforce agility, job satisfaction, work adjustment, and adversity questions are able to provide an optimal contribution in predicting the emergence of turnover among millennial employees after two years of work or before one year of the employment contract ends.